Did Chinese Outward Activity Attenuate or Aggravate the Great Recession in Developing Countries? - Bastian Gawellek; Jingjing Lyu; Bernd Süssmuth (Center for Economic Studies and ifo Institute (CESifo), 2016)
Using data on Chinese large-scale overseas investment and project contracts by sector, we analyze whether Chinese outward activity (COA) before the crisis worsened or alleviated the contractionary phases in developing countries. We find that, on average, COA did not increase vulnerability to the global recession. However, both the sectoral targeting and the size of the pre-crisis engagement matter: While COA in clearly to financial markets tied sectors implied an aggravation, substantial precrisis investment in the energy, metals and transportation industries implied an attenuation of the slump.
Keywords: F20; F30; F40; F63; 330; global crisis; offshoring; developing countries; sectoral transmission